Association of PNPLA3 rs738409 and TM6SF2 rs58542926 with health services utilization in a population-based study. Issue 1 (December 2015) - Köpp, Julia; Fleßa, Steffen; Lieb, Wolfgang; Markus, Marcello; Teumer, Alexander; Homuth, Georg; Wallaschofski, Henri; Marschall, Paul; Völzke, Henry; Baumeister, Sebastian
Abstract Background Hepatic steatosis confers an increased risk of metabolic and cardiovascular disease and higher health services use. Associations of the single nucleotide polymorphisms (SNP)PNPLA3 rs738409 andTM6SF2 rs58542926 with hepatic steatosis have recently been established. This study investigates the association betweenrs738409 andrs58542926 with health services utilization in a general population. Methods Data of 3759 participants from Study of Health in Pomerania (SHIP), a population-based study in Germany, were obtained. The annual number of outpatient visits, hospitalization and length of hospital stay was regressed onrs738409 andrs58542926 and adjusted for socio-economic factors, lifestyle habits, clinical factors, and health status. Results Minor allele homozygous subjects ofrs738409 had an increased odds of hospitalization as compared to major allele homozygous subjects (odds ratio [OR] 1.51; 95 % confidence interval [CI], 1.02 to 2.15). Heterozygous subjects did not differ from major allele homozygous subjects with respect to their odds of hospitalization. The three genotype groups ofrs738409 were similar with respect to the number of outpatient visits and inpatient days. Minor allele homozygous and heterozygous subjects ofrs58542926 had higher outpatient utilization (+53.04 % and +67.56 %, p  < 0.05, respectively) and inpatient days than major allele homozygous subjects. Conclusions After adjustment for several confounding factors, PNPLA3 rs738409 andTM6SF2 rs58542926 were associated with the number of outpatient visits, hospitalization, and inpatient days. Further studies are warranted to replicate our findings and to evaluate whether genetic data can be used to identify subjects with excess health services utilization.